Investigating burnout of Rehabilitation Medicine trainees: an Australian cross-sectional study - Michael W. Ponsford, MBBS; Justin L. Bilszta, PhD; Dean McKenzie, PhD; Bianca Fedele, BA (Psych)(Hons); John Olver, MD (The Journal of the International Society of Physical and Rehabilitation Medicine)
Background:. In Rehabilitation Medicine, there is an increased incidence of burnout compared with other specialties, with burnout affecting over 50% of rehabilitation physicians. There remains limited research investigating burnout in Rehabilitation Medicine trainees. Aim:. To investigate the frequency of burnout, and associations between burnout and workplace and demographic factors, among Australian registered Rehabilitation Medicine trainees. Methods. This cross-sectional study administered the Mini-Z Burnout Survey via the Qualtrics survey platform. The presence of burnout was determined on responses to Survey Item 3. Binary logistic regression evaluated associations between burnout presence and workplace and demographic (age, sex, and stage of training) variables. An open-ended question addressing workplace stresses underwent qualitative content analysis. Results:. Of the potential 220 registered trainees, 18.2% (39) consented to participate. Burnout was reported by 54.6% (18/33) of respondents with complete data. Logistic regression analyses revealed 2 Mini-Z items were significantly associated with burnout; job stress (odds ratio=22.9; 95% CI=3.5–145.8, P<0.001) and a hectic/chaotic work atmosphere (odds ratio=5.0; 95% CI=1.01–24, P=0.045). There was no significant association between burnout and the remaining Mini-Z items or between burnout and the demographic variables. Content analysis of responses to the open-ended question identified 3 themes: training issues; work place demands; personal health/work-life balance concerns. Conclusion:. This Australian-first study identified significant burnout in a cohort of Rehabilitation Medicine trainees. The sources of stress identified can be used to modify workplace environments and education requirements and promote well-being among trainees.